Circular Economy and Sustainability for the Provision of Drinking Water in Rural Areas. the Case of the Federation of Rural Drinking Water and Sanitation Cooperatives of Chile, Fesan - Radrigan-Rubio, M (Springer Nature, 2024)
Chile has a long tradition of providing drinking water and sanitation services through social economy organizations, dating back to the early 1960s. Since 1964, access to drinking water for rural sectors has been promoted especially through a health program to improve sanitary conditions and prevent diseases. A distinctive feature of drinking water and sanitation services provision in rural areas in Chile is that they are almost entirely provided by social economy organizations, such as cooperatives and rural drinking water committees, the latter recognized as part of the law on community organizations of a functional nature. Despite the achievements made in the last 60 years in terms of access to water in rural areas, the general system is currently subject to complex challenges, especially due to the regulatory framework governing water resources in Chile, which in practice defines it as a private good tradable based on market rules. In this context, it is becoming increasingly urgent for rural health services to adopt strategies guided by the principles of circular economy, both in terms of optimizing the use of water resources of their users and communities and in terms of a just energy transition, all in coherence with the new paradigm of the Circular Economy. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.